DIFFERENT TYPES OF UPPER EXTREMITY EXERCISE TRAINING IN DUCHENNE MUSCULAR DYSTROPHY: EFFECTS ON FUNCTIONAL PERFORMANCE, STRENGTH, ENDURANCE, AND AMBULATION - Alemdaroglu, Ipek; Karaduman, Ayse; Yilmaz, Oznur Tunca; Topaloglu, Haluk (My University, 2015)
IntroductionWe investigated and compared the effects of 2 different types of upper extremity exercise training on upper extremity function, strength, endurance, and ambulation in patients with early-stage Duchenne muscular dystrophy (DMD).